Divergent chemokine receptor expression and the consequence for human IgG4 B cell responses - Unger, P-PA; Lighaam, LC; Vermeulen, E; Kruithof, S; Makuch, M; Culver, EL; van Bruggen, R; Remmerswaal, EBM; Ten Berge, IJM; Emmens, RW; Niessen, HWM; Barnes, E; et al. (Wiley, 2020)
IgG4 antibodies are unique to humans. IgG4 is associated with tolerance during immunotherapy in allergy, but also with pathology, as in pemphigus vulgaris and IgG4‐related disease. Its induction is largely restricted to non‐microbial antigens, and requires repeated or prolonged antigenic stimulation, for reasons poorly understood. An important aspect in generating high‐affinity IgG antibodies is chemokine receptor‐mediated migration of B cells into appropriate niches, such as germinal centers. Here, we show that compared to IgG1 B cells, circulating IgG4 B cells express lower levels of CXCR3, CXCR4, CXCR5, CCR6, and CXCR7, chemokine receptors involved in germinal center reactions and generation of long‐lived plasma cells. This phenotype was recapitulated by in vitro priming of naive B cells with an IgG4‐inducing combination of TFH/TH2 cytokines. Consistent with these observations, we found a low abundance of IgG4 B cells in secondary lymphoid tissues in vivo, and the IgG4 antibody response is substantially more short‐lived compared to other IgG subclasses in patient groups undergoing CD20+ B cell depletion therapy with rituximab. These results prompt the hypothesis that factors needed to form IgG4 B cells restrain at the same time the induction of a robust migratory phenotype that could support a long‐lived IgG4 antibody response.